Joyful singing : a story of Lutheran sacred music in Texas - Kolodziej, Benjamin (Shaping American Lutheran church music, 2022)
In this volume, Kolodziej presents the story of the Lutherans who undertook the daunting and uncertain work of carving out a new life in a new land, and of the music that accompanied them. This is the tenth in a series of monographs--Shaping American Lutheran Church Music--published by the Center for Church Music, Concordia University Chicago.